E.T.A. Hoffman and Music - Schafer, R. Murray (Book collections on Project MUSE., 1975)
E.T.A. Hoffmann (1776-1822) was a man of diversified talents -- an artist, composer, conductor, critic, jurist, and writer. This book presents an over-all picture of romanticism in its incipient years.